Designing an Online Tutorial on Persistent Physical Symptoms: How Can We Deliver Teaching on a Complex but Vital Topic Within a Busy Medical Student Curriculum? - Jasmine Schulkind; Jahnavi Acharya; Joanne Davies; Kate Seddon (BJPsych Open)
Aims: Improve the knowledge and confidence of Year 4 Bristol medical students in assessing and managing patients presenting with persistent physical symptoms (PPS) through the delivery of an online teaching package.